Mass Media and Rural Out‐Migration in the Context of Social Change: Evidence from Nepal. (18th May 2010) - Piotrowski, Martin
Abstract This work examines the influence of mass media on rural out‐migration using historical and contemporary data from a setting experiencing massive social and economic development in the last half‐century. Data come from the Chitwan Valley Family Study, an ongoing study of an agrarian region in rural Nepal. Media are hypothesized to affect migration by inducing attitudinal and behavioural changes similar to those of other determinants of migration. As their influence differs from other determinants in important ways, media represent a unique form of influence that should be taken into account. I find that movie and television exposure are significant determinants of out‐migration in historical contexts, although television exposure was important in more contemporary contexts. Differences in these effects probably indicate the timing of the spread of each type of media and changing preferences among media consumers.